Bioresponsive albumin-conjugated paclitaxel prodrugs for cancer therapy - Jincheng Yang; Qingzhi Lv; Wei Wei; Zhengtao Yang; Jiajun Dong; Ruoshi Zhang; Qiming Kan; Zhonggui He; Youjun Xu (Taylor & Francis Group, 2018)
The efficacy of traditional chemotherapy often suffers from rapid clearance and off-target toxicity. Drug delivery systems and controlled release are applied to improve the therapeutic efficiencies of small-molecule drugs. In this work, two novel oxidative/reductive (Ox/Re) -sensitive and one non-sensitive Paclitaxel (PTX) prodrugs were synthesized with a maleimide group, which rapidly conjugates with albumin in vivo. Albumin serves as a good vehicle to deliver more prodrug to tumors due to the enhanced permeation and retention (EPR) effect. PTX was then released from the prodrugs in glutathione(GSH)/ reactive oxygen species(ROS)-rich tumor microenvironments. This bioresponsive prodrug strategy demonstrates potent chemotherapeutic efficiency in vivo and may be utilized in clinical cancer therapy.